A Time Partitioning Technique for Railway Line Design and Timetable Optimization. (26th February 2016) - Castillo, Enrique; Grande, Zacarías; Moraga, Paola; Sánchez‐Vizcaíno, Jesús
Abstract: Existing computer models used to optimize railway timetables lead to a high complexity when the number of analyzed services exceeds a given threshold. A time partitioning technique is proposed which allows line design and timetable optimization and a reduction in the complexity of the problem by considering small time windows of the same or different durations in which the timetables of a small (equal or not) number of running trains are optimized in sequence. Though the optimal solution is not expected to be attained with this method, the analyzed examples demonstrate that the resulting solution is close to the global optimum and practically satisfactory. This technique can be used at the planning and implementation stages. Examples of two real lines are analyzed to show the goodness of the proposed methods. One is the network Madrid–Sevilla–Toledo–Málaga–Valencia–Albacete with a dense traffic of 170 trains per day. The second is the Palencia–Santander line with 70 trains in which as an alternative to a double‐track proposal with a cost of M€ 3, 200 an alternate double–single‐track (ADST) solution, with a cost of M€ 330 (one tenth) is proposed.